Cancer and the Immune System: The History and Background of Immunotherapy - Abbott, Maura; Ustoyev, Yelena (Seminars in oncology nursing, 2019)
This article will outline the link between the immune system and cancer, and provide a historical timeline of immunotherapy developmental milestones. Published data and peer reviewed publications/manuscripts, and textbook chapters. Science has provided a greater understanding of the interactions between cancer and the human immune system. As this knowledge has grown, there has been significant progress in the development of clinically effective cancer immunotherapies. Nurses’ knowledge of the different types of immunity and the interaction of cancer cells with the immune system provides foundational knowledge for understanding cancer immunotherapy. Familiarity with the history of cancer immunotherapy will allow nurses to better comprehend why immunotherapy is now a pillar of cancer treatment that continues to develop. This knowledge will translate to better understanding and provision of care for patients receiving immunotherapy for the treatment of cancer.